Body mass changes during training in elite rugby union: Is a single test of hydration indices reliable?. Issue 8 (14th September 2018) - Black, Katherine Elizabeth; Black, Alistair David; Baker, Dane; Fairbairn, Kirsty
Abstract: There is limited research studying fluid and electrolyte balance in rugby union players, and a paucity of information regarding the test–retest reliability. This study describes the fluid balance of elite rugby union players across multiple squads and the reliability of fluid balance measures between two equivalent training sessions. Sixty-one elite rugby players completed a single fluid balance testing session during a game simulation training session. A subsample of 21 players completed a second fluid balance testing session during an equivalent training session. Players were weighed in minimal clothing before and after each training session. Each player was provided with their own drinks which were weighed before and after each training session. More players gained body weight (9 (14.8%)) during training than lost greater than 2% of their initial body mass (1 (1.6%)). Pre-training body mass and rate of fluid loss were significantly associated ( r  = 0.318, p  = .013). There was a significant correlation between rate of fluid loss in sessions 1 (1.74 ± 0.32 L h −1 ) and 2 (1.10 ± 0.31 L. h −1 ), ( r  = 0.470, p  = .032). This could be useful for nutritionists working with rugby squads to identify players with high sweat losses.